Effect of EGR on performance and emission characteristics of a dual fuel engine fuelled with CNG and JOME. Issue 6 (1st November 2016) - Kumar, Parvesh; Kumar, Naveen
ABSTRACT: The dual fuel engine shows significantly good results for brake thermal efficiency and brake specific energy consumption compared to the conventional diesel engine, at higher load. However, enhancements in NOx emissions were noticed. But it suffers with low thermal efficiency and high brake specific energy consumption, at low and intermediate loads. The application of exhaust gas recirculation (EGR) partially resolves the aforementioned problems of the dual fuel engine. In the present work, the dual fuel engine was operated with Jatropha oil methyl ester (JOME) as the pilot fuel for compressed natural gas (CNG). A comparative study has been done for various modes of operation: CNG-JOME dual fuel engine without EGR, CNG-JOME dual fuel engine with EGR, and conventional diesel engine at different operating loads. It was observed that the application of EGR improves the performance and emissions characteristics of the dual fuel engine compared to without EGR, particularly at low and intermediate loads. However, at higher loads, the use of EGR shows some adverse effect on performance and emissions characteristics, but decreased NOx emissions.